Hormones and Hearing: Central Auditory Processing in Women - Trott, Skylar; Cline, Trey; Weihing, Jeffrey; Beshear, Deidra; Bush, Matthew; Shinn, Jennifer (Journal of the American Academy of Audiology, 2019)
Estrogen has been identified as playing a key role in many organ systems. Recently, estrogen has been found to be produced in the human brain and is believed contribute to central auditory processing. After menopause, a low estrogen state, many women report hearing loss but demonstrate no deficits in peripheral hearing sensitivity, which support the notion that estrogen plays an effect on central auditory processing. Although animal research on estrogen and hearing loss is extensive, there is little in the literature on the human model.The aim of this study was to evaluate relationships between hormonal changes and hearing as it relates to higher auditory function in pre- and postmenopausal (Post-M) females.A prospective, group comparison study.Twenty eight women between the ages of 18 and 70 at the University of Kentucky were recruited.Participants were separated into premenopausal and peri-/Post-M groups. Participants had normal peripheral hearing sensitivity and underwent a behavioral auditory processing battery and electrophysiological evaluation. An analysis of variance was performed to address the aims of the study.Results from the study demonstrated statistically significant difference between groups, where Post-M females had difficulties in spatial hearing abilities as reflected on the Listening in Spatialized Noise Test–Sentences test. In addition, measures on the auditory brainstem response and the middle latency response reflected statistically significant differences between groups with Post-M females having longer latencies.Results from the present study demonstrated significant differences between groups, particularly listening in noise. Females who present with auditory complaints in spite of normal hearing thresholds should have a more extensive audiological evaluation to further evaluate possible central deficits.
Keywords: central auditory processing disorder; menopause